A tainted reputation it deserves? Crime in the trotting sector of Dutch horse racing - Reuselaars, Angelique (Trends in organized crime, 2021)
The Netherlands are a small country with an urban underworld history before a serious problem of organized crime has developed since the 1980. The interest of the mob in Horse Race Betting flourished before that time. After a long period of Prohibition since 1911 horse racing (especially trotting) and betting on the results has become a very popular pastime since it was permitted in 1948. Especially during the nineteen seventies and eighties horse races drew a large audience and to a lesser degree they still do. However, bookmaking has always been forbidden since 1911 and that by itself presented in invitation to (organized) crime. Other well-known criminal byproducts of horse racing such as drugging horses, laundering money and matchfixing have been observed but as we measured only to a very moderate degree. The social variety of aficionados for the races is amazing. While doing historical and ethnographic field research at the race tracks we registered a mixture of people of humble origins as well as big entrepreneurs. There were members of the royal family but also well-known criminals. It is amazing to find out to what degree the latter have been accepted by the entire horse racing community.